Measuring the Practicality of Science Process Skills-Based Electronic Student Worksheet: A Rasch Model Analysis - Risdalina, Risdalina; Rosmalinda, Desy; Pamela, Issaura Sherly; Putri, Andi Gusmaulia Eka (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
This study aims to measure the practicality of science process skills-based electronic student worksheet in the Biology and Environmental Concepts course of a Primary School Teacher Education Program at the University of Jambi. In this study, practicality refers to students' perceptions of ease of use, clarity of language, attractiveness of appearance, practicality in learning, practicality of science process skills-based activities, and efficiency of use. This study uses a quantitative descriptive approach involving 27 primary school education students as respondents. The research instrument is a questionnaire on the practicality of the electronic student worksheet consisting of 12 statements and analyzed using the Rasch Model with the help of Winsteps software. The Rating Scale Model was used because all items employed the same five-point response categories. The analysis was carried out to obtain the person and item reliability values, separation index, item suitability to the model, and mapping of respondent abilities and item difficulty levels. The results of the analysis show that the person reliability value is 0.82 (real) and 0.85 (model), with a Cronbach Alpha value of 0.93 which indicates the consistency of student responses in the very high category. The low item separation indicated limited spread of item difficulty and was interpreted as preliminary evidence of positive but homogeneous practicality perceptions rather than as definitive proof of broad usability. The person separation value of 2.14 (real) and 2.35 (model) indicates that the instrument is able to group respondents into three levels of practicality perception. All statement items were found to fit the Rasch Model with Infit and Outfit Mean Square (MNSQ) values ranging from 0.5 to 1.5. Wright mapping showed that the item difficulty level ranged from -0.62 to 1.10 logit and was below the average respondent's ability (mean person measure = 2.62 logit), indicating that the electronic student worksheet was generally easy to use and understand by students. Thus, the findings provide preliminary, context-bound evidence that the science process skills-based electronic student worksheet is practical for the sampled cohort and can be refined before wider implementation.